«Language game» as an universal game type - Baluta, Galyna (Actual Problems of Mind, 2017)
The author explains that each game classiﬁcation should include the language game as an initial (instrumental) precondition for the game of any kind, since the reality of a social game is organized as an hierarchy of types, including the level of a language game being fundamental.